Optimal heat and power management of a reversible solid oxide cell based microgrid for effective technoeconomic hydrogen consumption and storage. (1st August 2022) - Califano, M.; Sorrentino, M.; Rosen, M.A.; Pianese, C.
Highlights: A microgrid relying on a rSOC system as the main energy source is proposed. Development of a dual-state dynamic programming algorithm for the energy management. Optimization of electrical and thermal energies to satisfy the residential and vehicles needs. LCOE methodology used to assess the long-term advantages in adopting such solution. Abstract: This paper proposes and examines a highly integrated microgrid based on a reversible solid oxide cell, aimed at satisfying electrical and thermal loads of a 20-unit residential complex as well as the demands of electric and fuel cell vehicles. Such a system has been conceived as a profitable ready-made solution to be embedded into existing plants already equipped with renewable energy sources (i.e., wind farm and photovoltaic panels) by means of a reversible solid oxide cell and energy storage technologies. A dynamic programming-based routine has been suitably implemented as an algorithm for both the electrical and thermal sides of the plant for managing the power split indices. In addition, an external routine has been deployed to consider economic aspects; in particular, attention has been paid to the levelized cost of energy, allowing for comparisons with current reliable energy generation technologies. The analyses involve parametric assessments of multiple reversible solid oxide cell sizes and economic discount rates while fixing the lifetime of the plant at 30 years. In accordance with the results of the optimal microgrid design, by exploiting 100% of the rSOC working time (shared by mode as 40% fuel cell and 60% electrolyzer) a simple payback period of 5.97 years is achieved along with a levelized cost of energy index value in the 0.1 €/kWh-0.2 €/kWh range.